Powerpoint for Android Design Using Think Talk Write Model to Improve the Junior High School Studentsâ Concepts Understanding - Buchori, Achmad; Cintang, Nyai (Scientific Journal of Informatics, 2018)
As the development of Science and Technology also influence the development of learning media. Media learning is one of the determinants of student learning success. Utilization of android technology so far is not only used as a means of communication, or just entertainment but now can be developed for learning media. This research aims to develop powerpoint for android with Think Talk Write model to improve understanding of SMP students concept. The research method used is Research and Development and the type of research used is ADDIE. (1) Analyze, student needs analysis shows students need learning media. (2) Design, the products produced in this study media powerpoint for android. (3) Development, media developed then validated by 84% media experts, 82% material experts, and 85% design learning experts so it is said to be valid. (4) Implementation, student responses in class VII C achievement rate 89% are in the practical category. (5) Evaluation, the data in this study consists of preliminary data in the form of values obtained through pretest and final data in the form of values obtained through posttest. The result of the second posttest of the class is tested equality of two averages (right-t test) obtained Î± = 0.05 obtained t_table = 1.669 and t_count = 3.251 because Since t_count> t_table then H0 rejected and H1 accepted, so it can be concluded learning using Powerpoint for Android with Think Talk Write model to improve concept understanding is said to be valid, practical, and effective than the conventional learning model.